Dissemination of Gastroenterology and Hepatology Research on Social Media Platforms Is Associated With Increased Citation Count. (22nd October 2021) - Ayoub, Fares; Ouni, Ahmed; Case, Robert; Ladna, Michael; Shah, Harsh; Rubin, David T.
Abstract : INTRODUCTION: The purpose of this study was to find out whether dissemination of gastroenterology and hepatology (GI) research on social media networks correlates with citation count at 5 years. METHODS: We correlated the Altmetric Attention Score with Web of Science citation counts at 5 years for scholarly work published in the 10 highest impact factor GI journals in 2014. RESULTS: In 4, 026 analyzed items, the correlation ( r ) between Altmetric Attention Score and citations at 5 years was 0.62 ( P < 0.001), representing strong correlation. Twitter was the platform with the strongest correlation with citations. DISCUSSION: Social media attention garnered by GI scholarly work strongly correlates with the number of citations at 5 years.